This Time from Africa : Developing a relational approach to values-driven leadership - (:unkn) unknown (My University, 2023)
"The importance of relationality in ethical leadership has been the focus of recent attention in business ethics scholarship. However, this relational component has not been sufficiently theorized from different philosophical perspectives, allowing specific Western philosophical conceptions to dominate the leadership development literature. This paper offers a theoretical analysis of the relational ontology that informs various conceptualizations of selfhood from both African and Western philosophical traditions and unpacks its implications for values-driven leadership. We aim to broaden Western conceptions of leadership development by drawing on twentieth century European philosophy’s insights on relationality, but more importantly, to show how African philosophical traditions precede this literature in its insistence on a relational ontology of the self. To illustrate our theoretical argument, we reflect on an executive education course called values-driven leadership into action, which ran in South Africa, Kenya, and Egypt in 2016, 2017, and 2018. We highlight an African-inspired employment of relationality through its use of the ME-WE-WORLD framework, articulating its theoretical assumptions with embodied experiential learning."
Keywords: African Research